Answer:
g(-2) = -3, g(0) = -5 and g(3) = 22
Step-by-step explanation:
Here, the given function is:[tex]g(x) = 2x^2 + 3 x - 5[/tex]
Now, evalutaing the function at x = -2, 0 and 3
Substituting x = -2 in g(x):
[tex]g(-2) = 2(-2)^2 + 3 (-2) - 5 = 2(4) - 6 - 5 = 8 -11 = -3\\\implies g(-2) = -3[/tex]
Substituting x = 0 in g(x):
[tex]g(0) = 2(0)^2 + 3 (0) - 5 = 0 + 0 - 5 = -5\\\implies g(0) = -5[/tex]
Substituting x = 3 in g(x):
[tex]g(3) = 2(3)^2 + 3 (3) - 5 = 2(9) + 9 - 5 = 18 + 9- 5 = 27 -5 = 22\\\implies g(3) =22[/tex]
Hence, g(-2) = -3, g(0) = -5 and g(3) = 22.